Phalangopsidae crickets from Tropical Africa (Orthoptera, Grylloidea), with descriptions of new taxa and an identification key for African genera - Desutter-Grandcolas, Laure (Zootaxa, 2015)
New Phalangopsidae crickets are described from tropical Africa, including three new genera and ten new species: Afrophaloria Desutter-Grandcolas, n.gen., Afrophaloria amani Desutter-Grandcolas, n. sp., type species, Afrophaloria apiariensis Desutter-Grandcolas, n. sp., Afrophaloria hempae Desutter-Grandcolas, n. sp., Kameruloria gabonensis Desutter-Grandcolas, n. sp., Kameruloria nigricornis Desutter-Grandcolas, n. sp., Kameruloria trimaculata Desutter-Grandcolas, n. sp., Paragryllodes amani Desutter-Grandcolas, n. sp., Phasmagryllus Desutter-Grandcolas, n.gen., Phasmagryllus elegans Desutter-Grandcolas, n. sp., type species, Upupagryllus Desutter-Grandcolas, n.gen., Upupagryllus subalatus Desutter-Grandcolas, n. sp., type species, and Upupagryllus alatus Desutter-Grandcolas, n. sp. All these taxa, except Paragryllodes amani Desutter-Grandcolas, n. sp., belong to the subfamily Phaloriinae. The subfamily is redefined, to take into account their morphological (apterous taxa) and ecological (straminicolous taxa) diversity. A key for phalangopsid African genera is proposed, and the status of Larandeicus Chopard, 1937 briefly discussed.